Prognostic factors for patients with newly diagnosed brain metastasis from breast cancer. (May 2015) - Castaneda, Carlos A; Flores, Raymundo; Rojas, Katerin Y; Castillo, Miluska; Dolores-Cerna, Ketty; Flores, Claudio; Belmar-Lopez, Carolina; Milla, Esperanza; Gomez, Henry
SUMMARY : Aim: This retrospective study determined features associated with brain metastasis (BM) in women with breast cancer.Patients & methods: A total of 215 initially early breast cancer cases were included. We reviewed files and CT scan images of BM.Results: Median age was 47 years and most of our cases were stage III (58.6%), grade III (62.8%), ER negative (62.3%) and nonluminal (59.1%). Median survival after BM was 4 months. Nonluminal, extracranial disease, time to CNS shorter than 15 months, >three brain lesions and poor breast-graded prognostic assessment and recursive partitioning analysis scores were associated with shorter survival. Adding extracranial disease to breast-graded prognostic assessment score also predicted survival after BM. Radiation response was assessed in 57 patients and response tended to be associated with nonluminal phenotype but not with survival.Conclusion: Factors associated with both initial tumor and clinical features at BM time are associated with shorter survival in our Latinas population.